Design of Polarization-Independent Coarse Wavelength Splitters Based on Ridge-Waveguide Directional Couplers - Chee-Wei Lee (International Journal of Optics)
We present the first unique design of a polarization-independent dual-wavelength splitter for wavelengths around 1.3 μm and 1.55 μm that is potentially of great interest to passive optical network (PON) applications. The filter design is simple compared with the other architectures and is based on ridge-type lateral directional couplers that can be readily integrated with other planar waveguide devices. Two design examples, based on InP/InGaAsP and Si/SiGe waveguides, are given. This polarization-independent wavelength splitting is achieved by exploiting the polarization dependence of the waveguides to produce coupling lengths that are sensitive to polarization and wavelength. We show that, to split the wavelengths without splitting the polarizations, the coupling lengths must be sufficiently different for TE and TM and for the different wavelengths in order to give the correct required ratios between the TE and TM coupling lengths for the two wavelengths of interest. We also show that the same approach can be applied to the design of a polarization splitter. The crosstalk, optical bandwidth, and fabrication sensitivity for the wavelength filter are evaluated.